ANALISIS AKIBAT DARI PEMALSUAN DOKUMEN PERKAWINAN DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 DAN HUKUM ISLAM - Aufa Putri Nabila; Mia Hadiati (Jurnal Hukum Adigama, 2022)
Every citizen has the right to marry because this marriage is a sacred event so that there are manylegal responsibilities. This is stated in Article 1 of Law Number 1 of 1974 concerning Marriage whichstates "Marriage is an inner and outer bond between a man and a woman as husband and wife withthe aim of forming a happy and eternal family (household) based on the One Godhead. ." So we need alegal regulation itself that regulates marriage law so as not to cause a problem in the future. This legalarrangement of marriage must be focused first on the registration of marriages because theregistration of marriages is very important for the continuity of the parties who have carried out themarriage procession. An unregistered marriage will have legal consequences for the position of thewife, the position of the children, and the position of assets. A marriage that has occurred must berecorded because this is an ef ort made by the government to create order in an administration in thefuture.